STUDY ON DEVELOPMENT OF GLUTAMIC ACID AND SODIUM DODECYL SULFATE MODIFIED CARBON PASTE ELECTRODES FOR VOLTAMMETRIC ANALYSIS OF CAPSAICIN - Septian, Doni
Capsaicin consumption below 500 ?M gives anti-cancer and anti-obesity benefits. However, higher levels consumption of capsaicin can accelerate the growth of cancer cells. Therefore, an analytical method is needed to measure capsaicin levels to reach the expected detection limit. Voltammetric measurement of capsaicin has been carried out with carbon-based electrodes with modifications that are relatively difficult and take a long term, such as modificated by printed polymers and modificated by dopants. Carbon paste electrode (CPE) is an inexpensive but has low-sensitivity carbon-based electrode. CPE modification is needed to increase sensitivity with simpler modification. Electropolymerization of glutamic acid on the surface of CPE can increase the sensitivity of capsaicin measurement due to the hydrophobic interaction between poly-(glutamic acid) (PGA) and capsaicin. Sodium dodecyl sulfate (SDS) can shift the value of glutamic acid oxidation potential during electropolymerization and also dissolve residues on the surface of CPE resulting from radical reaction, so that glutamic acid can stick to the surface of CPE before electropolymerization takes place. This research is a literature review on the development of PGA and SDS modified CPE for voltammetric analysis of capsaicin. Several parameters that need to be studied include: the optimum concentration of SDS, the optimum number of cycles of electropolymerization, the selection of electrolytes, the optimum pH of the electrolyte, and the voltammetric technique used. Based on the literature review, the optimum concentration of SDS for the electropolymerization process is 10 mM. The optimum number of cycles for electropolymerization of glutamic acid is predicted until 12 cycles to prevent PGA thickening. Britton-Robinson buffer was chosen as the electrolyte solution because it has good solubility with capsaicin and also maintains the pH value of the solution. The optimum pH value of the electrolyte is in ranges 4.45-9.93. When the pH value of the electrolyte exceeds 9.93, the hydroxyl group of capsaicin undergoes transformation into o-methoxyphenate species which results in the absence of an anodic oxidation peak of capsaicin. Based on the results of the literature review, the measurement of capsaicin using the cyclic voltammetry technique is predicted to be a better technique qualitatively than other voltammetric techniques. Based on the literature review, measurement of capsaicin with PGA and SDS modified CPE expecting can be detected until reach detection limit 0,02-0,5 ?M.